EFFICACY AND SAFETY OF FIXED COMBINATION OF LISINOPRIL AND HYDROCHLOROTHIAZIDE FOR MANAGEMENT OF VASCULAR DISORDERS IN PATIENTS WITH ARTERIAL HYPERTENSION - L. A. Haisheva (Столичная издательская компания, 2016)
Aim. To study endothelial disorders and artery elasticity disorders in patients with arterial hypertension (HT), as well as possibility of their correction by lisinopril or by fixed low dose combination of lisinopril and hydrochlorothiazide. Material and methods. 99 patients with HT were included in the study. Patients were randomized into 2 groups. Patients of the 1st group were treated with the fixed low dose combination of lisinopril (5мг) and hydrochlorothiazide (12,5 mg). Patients of the 2nd group were treated with lisinopril alone. The amlodipine was added in case of insufficient therapy. Pulse wave velocity was defined by volume sphygmography. Tests for evaluation of microalbuminuria and activity of von Willebrand factor were performed. Results. Endothelium function disorders were observed in a half of the patients with HT aged 60 y.o. and older. The fixed low dose combination of lisinopril and hydrochlorothiazide was more effective than lisinopril monotherapy in target blood pressure achievement. Positive changes of endothelium function indicators were founded in both groups of therapy. This fixed combination had also a good safety profile. Conclusion. Lisinopril alone or in low dose combination with hydrochlorothiazide improves endothelium function and decreases microalbuminuria level in patients with HT and high body mass index.